Efficacy of stereotactic body radiotherapy in oligorecurrent and in oligoprogressive prostate cancer: new evidence from a multicentric study - Triggiani, Luca; Lohr, Frank (British journal of cancer, 2017)
Background:The aim of the present study is to evaluate the impact of metastases-directed stereotactic body radiotherapy in two groups of oligometastatic prostate cancer (PC) patients: oligorecurrent PC and oligoprogressive castration-resistant PC (oligo-CRPC).Methods:Inclusion criteria of the present multicentre retrospective analysis were: (1) oligorecurrent PC, defined as the presence of 1-3 lesions (bone or nodes) detected with choline positron emission tomography or CT plus bone scan following biochemical recurrence; (2) oligo-CRPC, defined as metastases (bone or nodes) detected after a prostatic-specific antigen rise during androgen deprivation therapy (ADT). Primary end points were: distant progression-free survival (DPFS) and ADT-free survival in oligorecurrent PC patients; DPFS and second-line systemic treatment-free survival in oligo-CRPC patients.Results:About 100 patients with oligorecurrent PC (139 lesions) and 41 with oligo-CRPC (70 lesions), treated between March 2010 and April 2016, were analysed. After a median follow-up of 20.4 months, in the oligorecurrent group 1- and 2-year DPFS were 64.4 and 43%. The rate of LC was 92.8% at 2 years. At a median follow-up of 23.4 months, in the oligo-CRPC group 1- and 2-year DPFS were 43.2 and 21.6%. Limitations include the retrospective design.Conclusions:Stereotactic body radiotherapy seems to be a useful treatment both for oligorecurrent and oligo-CRPC.